2021
DOI: 10.1002/ccr3.4236
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant tissue‐type plasminogen activator treatment in an extremely low birth weight infant

Abstract: Tissue plasminogen activator can effectively treat clinical thrombosis in premature infants 11 hours after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Bolus dose of rt-TPA was administrated in nine cases with a dosage range of 0.05–1 mg/kg intravenously 14 15 18–21 24. We found that the following continuous infusion of rt-TPA was highly heterogeneous both in terms of dosage (range 0.01–1.2 mg/kg/hour)13 23 and duration (range 1–13 days) 13–15 18 19 21 23. Low-dose rt-TPA was given to 16 of 28 neonates,13–18 20 22 24 while the remaining subjects received high-dose rt-TPA 13 14 18 19 21 23.…”
Section: Commentarymentioning
confidence: 96%
See 3 more Smart Citations
“…Bolus dose of rt-TPA was administrated in nine cases with a dosage range of 0.05–1 mg/kg intravenously 14 15 18–21 24. We found that the following continuous infusion of rt-TPA was highly heterogeneous both in terms of dosage (range 0.01–1.2 mg/kg/hour)13 23 and duration (range 1–13 days) 13–15 18 19 21 23. Low-dose rt-TPA was given to 16 of 28 neonates,13–18 20 22 24 while the remaining subjects received high-dose rt-TPA 13 14 18 19 21 23.…”
Section: Commentarymentioning
confidence: 96%
“…Reviewing the literature, 12 studies which reported 28 very or extremely preterm neonates who had pharmacological thrombolysis with rt-TPA for intracardiac thrombi were found13–24 (table 1). Their GA ranged from 23 to 31 weeks14 25 with a birth weight from 544 to 1300 g 13 21. The age at diagnosis of thrombosis was from 1 to 54 days of life 18 20.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations